Janus structured multiwalled carbon nanotube forests for simple asymmetric surface functionalization and patterning at the nanoscale - Quinson, J; Dillon, F; Nicholls, R; Koos, A; Vincent, K; Grobert, N (American Chemical Society, 2020)
The asymmetric functionalization of nanomaterials is desired to develop nanostructures with increasingly exotic properties. Nevertheless, it remains a general challenge and a difficult task. Janus structured multiwalled carbon nanotubes with intratubular junctions between undoped and nitrogen-doped sections have been exclusively considered to date for electronic applications in studies typically requiring only few individual nanotubes. Such structures are here shown to be suitable scaffolds to simply achieve a spontaneous, asymmetric and localized functionalization and patterning at the nanoscale. First, a method to produce large quantities (>100 mg per experiment) and long (>100 μm) vertically aligned multiwalled carbon nanotube forests by a hybrid aerosol assisted and traditional chemical vapor deposition is presented. Scanning and transmission electron microscopy, electron energy loss spectroscopy and Raman spectroscopy characterizations confirm a continuous intratubular transition between nitrogen-doped and undoped sections. Second, and for the first time, the described Janus structures are shown to be suitable scaffolds to achieve an asymmetric, spontaneous and yet spatially controlled reactivity along nanotubes. This is illustrated with the examples of asymmetric oxidation properties and asymmetric immobilization of platinum nanoparticles. Asymmetric functionalization is simply achieved by carefully controlling and exploiting the different surface properties along the Janus structured carbon nanotubes.